PERANCANGAN TEORITIS PLTS TERPUSAT SEBAGAI ALTERNATIF SUPLAI LISTRIK KEBUTUHAN SUCKER ROD PUMP - Kartikasari, Pinky; Hatuwe, Azmain Noor; Lilipaly, Eka R. M. A. P. (Jurusan Teknik Mesin, 2024)
Design of PLTS is an effort to enhance the reliability of electrical power, electrification ratio, and utilization of renewable energy in the oil and gas industry. The availability of electricity is extremely urgent to meet the production process requirements, particularly for the motor-driven SRP pumping system. Currently, the industry relies on PLN and genset electricity for daily production activities. However, the design of a centralized PLTS system is expected to meet the SRP electricity needs in the oil and gas industry. The power grid in the oil and gas industry is obtained from PLN and genset. Therefore, the need for a power plant is evident. Related to the research previously discussed with the title â€œDesign of Centralized PLTS as an Alternative Electricity Supply for Sucker Rod Pumpâ€ (Pinky Kartikasari, 2024), this study aims to determine the capacity of panels and batteries required for the development of a centralized PLTS in the oil and gas industry. The method used in this research is quantitative because it involves calculating the capacity of solar panels, daily energy needs, and numerical system analysis. The results show that the total energy requirement for SRP electricity supply is 264 kWh/day. The required capacity of panels is 106 kWp, with a total of 200 monocrystalline panels each with a capacity of 550 Wp. Additionally, there are 128 batteries with a capacity of 24V 200Ah. The inverter used is the PV1800 ECO Series 6.200W type, with 20 units in total. Keywords: PLTS (Solar Power Plant), SRP (Sucker Rod Pump), Oil and Gas Industry